The Influence Of Giving Fertilizer And Fertilizer (N) Fertilizer Time On Plant Growth And Production Sawi Pakcoy (Brassica rapa L.) - Abdul Wachid; Achmad Sairi (Universitas Muhammadiyah Sidoarjo, 2018)
The average pakcoy mustard production in Indonesia is still quite low at 20 tons / ha. This study aims to determine the effect of goat manure and nitrogen fertilizer (N) on the growth and production of mustard greens. This research was carried out in Plaosan village, Wonoayu sub-district, Sidoarjo regency, using factorial completely randomized design with 2 factors, factor 1: without goat manure (control) (P0), goat manure 100 grams / polybag (P1 ), 200 gram goat manure / polybag (P2). Factor 2: giving nitrogen at 7 hst (K1), giving nitrogen at 14 hst (K2), giving nitrogen at 21 hst (K3). Of the two factors, 9 treatment combinations were repeated and repeated 3 times so that 27 experimental units were obtained. The results showed that goat manure significantly affected plant height, number of leaves and wet weight. However, when giving nitrogen (N) there was no significant difference in each treatment, while there was interaction between goat manure and nitrogen (N) fertilization time on the wet weight of mustard pakcoy plants with the best treatment in K2P2 with an average of 231,8.